Design Of Advanced Controllers Used In Multivariable Process - Mr. M. Nagarajapandian., Mrs. T. Anitha, S. Prithivi Lakshmi (International Journal of Advanced Science and Technology, 2020)
There are numerous frameworks on the planet which  are non-straight in nature. A large portion of the businesses depended on just the single circle control to direct such procedures. Structure of multi variable framework is of incredible interest in process enterprises. The four tank framework is multivariable procedure which is non-straight and dynamic in nature. This framework adheres to that the law of mass parity conditions and vitality conditions. In four tank framework, it is hard to keep up the degree of tank because of the communications between the procedure factors. In the current strategy, there are numerous controllers accessible for four tank framework to keep up the water level of the tank. In any case, every one of the controllers won't be suitble for execution and the precision in the yield during implementation is questionable .So in this undertaking the controllers,such as Proportional Integral(PI) , Linear quadratic Gaussian Controller(LQG) are planned, mimicked and perfomance of the controller are looked at by following parameters like peak  time,peak overshoot, rise time and steady state error.